The Effect of Applying the Problem-Posing Learning Model on Learning Outcomes of Set Material in Middle School Students - Falentino Polii; Ichdar Domu; Vivian Eleonora Regar (Journal on Education, 2024)
This research aims to determine the differences in student learning outcomes in junior high school after receiving learning using the Problem-posing model and the direct learning model on Association material. The research method used in this research is a quasi-experiment with a Posttest Only Control Design by applying the Problem Posing learning model and the Direct learning model. In this research, the author used two sample classes, namely VIIA, using the Problem-solving learning model as the experimental class, and VIIB, using the direct learning model as the control class. The instrument used is four descriptive questions whose validity and reliability have been tested and scored. The results of data analysis show that the average student learning outcomes in the experimental class are 80.20 higher than the average student learning outcomes in the control class, namely 75.95; this indicates differences in student learning outcomes in the set metrics by applying the Problem-posing learning model. The results of data analysis using the Liliefors test and t-test show that the data obtained in this study is normally distributed, which means that applying the Problem-posing learning model influences students' ability to solve Association questions at St. Catholic Middle School. Johanis Laikit.